2022
DOI: 10.7759/cureus.32178
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Patterns, and Risk Factors of Work-Related Musculoskeletal Diseases Among Teachers in the Eastern Province, Saudi Arabia: A Community-Based Retrospective Cross-Sectional Survey

Abstract: Background and objectiveWork-related musculoskeletal diseases (WMSDs) are one of the most common occupational health concerns among teachers. They refer to a variety of degenerative and inflammatory disorders that can be triggered by the work environment of the people affected. Teachers' health is substantially significant as it impacts their productivity at work. The aim of this study was to determine the prevalence, patterns, implications, and risk factors of WMSDs among teachers in the Eastern Province of S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
2
0
0
Order By: Relevance
“…Low back pain (44.6%) and neck pain (40.1%) were the most frequently reported complaints among students in the past twelve months in our study, which is similar to a conclusion reached by a study performed in Al-Qassim in 2021 [13]. In another study done in Saudi Arabia, more severe symptoms were encountered based on the duration of working hours [14]. However, our study showed that there was no significant correlation between studying hours, which constitute a student's workload, and MSK pain.…”
Section: Discussionsupporting
confidence: 91%
“…Low back pain (44.6%) and neck pain (40.1%) were the most frequently reported complaints among students in the past twelve months in our study, which is similar to a conclusion reached by a study performed in Al-Qassim in 2021 [13]. In another study done in Saudi Arabia, more severe symptoms were encountered based on the duration of working hours [14]. However, our study showed that there was no significant correlation between studying hours, which constitute a student's workload, and MSK pain.…”
Section: Discussionsupporting
confidence: 91%
“…The prevalence of WMSDs in the elbows area among schoolteachers in the UAE is relatively lower at 16%. This nding is supported by a recent study conducted in Saudi Arabia[15]. Although the speci c reasons for this lower prevalence require further investigation, it could be attributed to the nature of teaching tasks that involve fewer repetitive or forceful movements involving the elbows.…”
supporting
confidence: 68%